Young Women's Experiences as Consumers of Maternity Care in Queensland - Redshaw, M; Miller, Y; Hennegan, J (Blackwell Publishing Inc., 2014)
Background: Young motherhood is commonly associated with vulnerabilities, stereotyping of young women's behavior, and poor outcomes for them and their children. The objective was to understand how maternity care is experienced by this group in the transition to parenthood. Methods: Data from a large-scale 2010 survey of women's experience of maternity care were analyzed using qualitative methods with open text responses. Results: Overall, 7,193 women responded to the survey: 237 were aged 20 years or less. Most (83%) of these young women provided open text responses. The main themes were: "being a consumer," "the quality of care," "needing support," and "pride in parenthood" whereas subthemes included "being young" and "how staff made me feel," "testimonials for staff," "not being left," and "it is all worthwhile." Conclusion: Many young women responding described a positive experience. For many first-time mothers this feeling marked a change in their identity. Nevertheless, staff perceptions and attitudes affected how they saw themselves and what they took away from their experience of maternity care. A key message for other women is offered, supporting and reinforcing their role as active and involved consumers who, in engaging with services, have to stand up for themselves and make their needs and wishes known. © 2014, Wiley Periodicals, Inc.